2012
DOI: 10.4414/smw.2012.13595
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards transplantation and medication among 121 heart, lung, liver and kidney recipients and their spouses

Abstract: The attitudes of patients and spouses to different aspects of the transplant itself and to being a transplant patient or spouse should be deliberately reconsidered and facilitated in the psychosocial counselling with regard to the comprehensibility, manageability and meaningfulness of the transplant experience as well as to potential conflicts in the partnership.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
0
19
0
1
Order By: Relevance
“…This cross-sectional study was part of a larger project on the physical and psychological conditions of transplant patients and their partners (see [19,20] 1 . Inclusion criteria for patients were a heart, liver, kidney or lung transplant surgery at the University Hospital Zurich, Switzerland at least 6 months previously, sufficient knowledge of the German language, and the willingness of a partner or spouse to also take part in the study.…”
Section: Sample and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This cross-sectional study was part of a larger project on the physical and psychological conditions of transplant patients and their partners (see [19,20] 1 . Inclusion criteria for patients were a heart, liver, kidney or lung transplant surgery at the University Hospital Zurich, Switzerland at least 6 months previously, sufficient knowledge of the German language, and the willingness of a partner or spouse to also take part in the study.…”
Section: Sample and Designmentioning
confidence: 99%
“…The attitudes towards immunosuppressive medication scale was newly developed for this study [20] and assessed with four items. The items were rated on a semantic differential following the stem 1 Data from this research project have been published before.…”
Section: Attitudesmentioning
confidence: 99%
“…Research has shown that relatives of patients waiting for heart or lung transplantation worried about a rapid disease progression and death while the patient was waiting for new organs (7,8). Most relatives suffer from uncertainty, fear and stress (7)(8)(9). These emotions persist after the transplantation, during the recovery period, and in some cases for years because of the risk of acute, or in the long term, chronic organ rejection and death (10).…”
Section: Introductionmentioning
confidence: 99%
“…Transplant patients and their relatives felt that they had experienced something unique at the same time, which might contribute to a positive connectedness (9). Therefore it is important that healthcare professionals understand that patients and relatives undergo the process together (19).…”
mentioning
confidence: 99%
“…Poor physical health in the caregiver at 12 months after transplantation results in a lower patient survival during the next seven years [343]. After HT, considering the consequences on the psychophysical health and socio-economic level of caregivers, some authors have identified the need for psychological support to the family [344] and for psychotherapeutic interventions addressed to the family [345]; others, focusing on potential conflicts in the marital relationship, suggest the utility of psychosocial interventions of counseling addressed to the couple [346,347].…”
Section: ) Family Caregivers Of Patients Undergoing Heart Transplantmentioning
confidence: 99%